Levan enhanced the NF-kappa B suppression activity of an oral nano PLGA-curcumin formulation in breast cancer treatment - TOKSOY ÖNER, EBRU; EROĞLU, MEHMET SAYIP (ELSEVIER, 2021)
Chemoresistance (CR) is one of the reasons why chemotherapy agents like Gemcitabine (GMC) remain insufficient in healing breast cancer. Activation of Nuclear Factor-kappa B (NF-kappa B) during chemotherapy is known as an important factor in the development of CR. The hydrophobic polyphenol curcumin is shown to inhibit NF-kappa B and hence CR. The aim of this work was to increase the poor bioavailability of curcumin by loading it into the nano-micelles made of Poly (Lactide-co-Glycolide) (PLGA) and levan, where levan as a natural fructose homopolymer makes the nano-micelle more stable and increases its uptake using the fructose moieties. In this study, a PLGA-levan-curcumin formulation (PLC) was designed and characterized. The size was measured as 154.16 +/- 1.45 nm with a 67.68% encapsulation efficiency (EE%). The incorporation between the components was approved. Levan made the nano-micelles stable for at least three months, increased their uptake, and led to a 10,000-fold increase in the solubility of curcumin. The enhanced bioavailability of curcumin reduced the NF-kappa B levels elevated by GMC, both in vitro and in vivo. The PLC showed a complete tumor treatment, while GMC only showed a rate of 52%. These point to the great potential of the PLC to be used simultaneously with chemotherapy.
Keywords: Levan; Curcumin; Gemcitabine; NF-kappa B; Oral nano drug delivery; PLGA; PANCREATIC-CANCER; GEMCITABINE; NANOPARTICLES; MODEL; INHIBITION; SOLUBILITY; COPOLYMER; APOPTOSIS; MICELLES; CELLS